Intellectual Capital Disclosures and Corporate Governance in Gaining the Firms’ Non-Discretionary Profits and Market Value in ASEAN-5 - Hatane, Saarce Elsye; Nathania, Felicia; Lamuel, Jocelyn; Darusman, Fenny; Devie, (Organizations and Markets in Emerging Economies, 2020)
This study aims to find the effect of Intellectual Capital Disclosure (ICD) and Corporate Governance (CG) on firm performance in ASEAN countries. Firm performance is divided into accounting-based performance and market-based performance. The accounting-based performance consists of Non-Discretionary Net Income (NDNI) and Cash Flow Operations (CFO), while market-based performance consists of Tobin’s Q and Market-to-Book Ratio (MBR). The measurement of ICD components uses a scoring system. The sample of this research is 112 firms in the industrial technology listed in the stock exchange of ASEAN-5 between 2011 and 2018. This study finds that NDNI increases when firms increase RCD quality. No ICD components are capable of affecting CFO. On the other hand, SCD is a variable that decreases NDNI value. BGEN is found to reduce NDNI and CFO values. RCD is also the only ICD component that can increase market-based performance, especially MBR. HCD consistently lowers the values of MBR and Tobin’s Q. BSIZE holds a significant role in raising Tobin’s Q score, and BGEN lowers MBR instead. BIND has no part in the market-based performance, but it significantly lowers NDNI value. This study adds another view to ICD’s benefits from two firm performance perspectives, accounting-based performance and market-based performance, especially in ASEAN-5.
Keywords: Non-discretionary Net Income; Accounting-based Performance; Market-based Performance; Intellectual Capital Disclosure; Good Corporate Governance